Enhancing companies’ competitivity through trade fairs: a set of articles - Silva, Pedro Bruno Mendonça da (2023)
Trade Fairs are a marketing tool that offers networking, entrepreneurship, export, sales, and high-quality information opportunities. In practice, trade fairs are systems of multiple exchanges between participants. In a trade fair context, all companies/exhibitors try to remain profitable and outperform their competitors while facing diverse challenges. This study demonstrates how exhibitors’ intelligence activities and entrepreneurial orientation can generate results and improve their competitiveness. Thus, the present dissertation groups together a set of studies that can be used by exhibitors to make their participation in such events successful, improving their position in the market. This thesis consists of four scientific essays organized in six chapters. The present Introduction focuses first on the argumentation of the study and explains the methodologies used. Chapter 1 seeks to examine the role of Trade Fair Intelligence Activities within the perspective of exhibitors. Chapter 2 shows that Entrepreneurial Orientation emerged from the literature as an excellent determinant for the development of business competence. The purpose of this particular research is to examine the influence of Entrepreneurial Orientation on the Network and the Exhibitor’s Performance. Chapter 3 studies specifically a dimension of Entrepreneurial Orientation: product innovation. The purpose of this particular research is to examine the relationship between product innovation and network, and their export performance in a trade fair context within the exhibitor’s perspective, more concretely SMEs (Small and Medium Enterprises). Chapter 4 examines the impact of the exhibitors’ sales force proactiveness (another dimension of Entrepreneurial Orientation) on their network capability and sales performance. Lastly, the present dissertation ends with general conclusions, where contributions, implications and general limitations are discussed. The conclusion ends with suggestions for future research. Generally, the research shows that Intelligence Activities and the practices that characterize Entrepreneurial Orientation can occur in parallel in a trade fair context. During trade fairs there are several sources of information (customers, product and market) that can be observed, collected and analysed. Intelligence activities in a trade fair context can provide insights not available elsewhere, that warn of potential marketing threats and opportunities, thus contributing to the competitiveness of the company/exhibitor. The examination of entrepreneurial orientation in trade fairs’ context revealed that the exhibitor, when thinking and behaving in an entrepreneurial way (Innovativeness; Proactiveness; Risk-Taking; Competitiveness; Autonomy), improves business performance, especially when network capabilities are well developed. The study also highlights the dimensions of innovation and proactivity with implications for short-term financial return (sales performance) and long-term business growth (export performance). Although research studies have been carried out on success factors for exhibitors, this study is a pioneer in addressing intelligence activities and entrepreneurial orientation in a trade fair context, as factors of success and competitiveness for exhibitors. The research becomes even more relevant when considering the current economic dynamism shaped by the rapidly changing technological, social, political and economic environment. Therefore, based on these aspects, this study can be considered new and original.